Chains ebook - Anderson, Laurie Halse (Seeds of America, 2011)
From acclaimed author Laurie Halse Anderson comes this compelling first novel in the historical middle grade The Seeds of America trilogy that shows the lengths we can go to cast off our chains, both physical and spiritual. As the Revolutionary War begins, thirteen-year-old Isabel wages her own fight...for freedom. Promised freedom upon the death of their owner, she and her sister, Ruth, in a cruel twist of fate become the property of a malicious New York City couple, the Locktons, who have no sympathy for the American Revolution and even less for Ruth and Isabel. When Isabel meets Curzon, a slave with ties to the Patriots, he encourages her to spy on her owners, who know details of British plans for invasion. She is reluctant at first, but when the unthinkable happens to Ruth, Isabel realizes her loyalty is available to the bidder who can provide her with freedom.